Dismantling The Ideology Of The Film Budi Pekerti (Discourse on Character and Morality Education on the Big Screen) - Nurapni Pebyyani; Amin Aminudin (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines the ideological discourse embedded in the 2023 film Ethics, with a focus on the depiction of character education and morality. Through critical discourse analysis, this research identifies how films build moral values, representations of ethical dilemmas, and ideological messages conveyed to the audience. This research highlights the role of film in shaping public perception of ethics and character education. Furthermore, this research explores how film narratives engage with traditional and modern perspectives on moral values. Using Van Dijk's critical discourse analysis, this study investigates how Ethics builds its ideological attitudes and the implications of its moral representations. The film is positioned in a larger discourse than Indonesian cinema as a tool for moral storytelling, emphasizing its potential in shaping societal norms. The study also discusses how audiences interpret the moral and ethical dilemmas presented, taking into account the socio-cultural context of Indonesia. The findings of the study show that Ethics strengthens the importance of character education through the depiction of ethical struggles, depicting individual and systemic moral conflicts. This highlights the film's dual function: as a reflection of contemporary moral values and as a critique of the ethical tensions prevailing in Indonesian society.